Pengaruh Tingkat Pendidikan Aparat Kecamatan Dengan Kinerja Pelayanan Pada Kantor Kecamatan Kajuara Kabupaten Bone - Muhlis Hajar Adiputra; Suardi Mukhlis (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2022)
This paper aims to find out how the level of education of sub-district officials with service performance at the Kajuara District office, Bone Regency. The type of research used is quantitative research with a survey approach, which is research that takes a sample from one population and uses questionnaires as a data measurement tool. Data collection techniques through questionnaires (questionnaire) and documentation. This study used a sample of 100. The results of the study (1) The level of education of sub-district officials with service performance at the Kajuara District office, Bone Regency, influenced each other or had a good influence (2) Several factors influenced the education level of sub-district officials with service performance at the K ajuara District office. Bone is one of the factors of education up to high school and undergraduate.